Investigation of co-milling Utah bituminous coal with prepared woody biomass materials in a Raymond Bowl Mill. (15th June 2018) - Dobó, Zsolt; Fry, Andrew
Abstract: The operational performance of a Combustion Engineering 312 Raymond Bowl Mill has been investigated while milling a blend of Utah bituminous coal and prepared Manti-La Sal woody biomass. The research focuses on identifying the differences between the various biomass pretreatment methods regarding to co-milling behavior in a pilot scale bowl mill. Torrefied chips, torrefied pellets and steam exploded pellets were evaluated with a mass ratio of 15% biomass and 85% coal and compared to the measured pure coal mill performance. The milling process was monitored by recording the mill power requirement, inlet and outlet temperatures, fluidization air flow rates, fuel moisture content, milled product particle size distribution and SEM analysis of the particles. It was found that the blend with steam exploded pellets is the most suitable for co-milling due to it shows particle size distribution (PSD) close to the case of 100% coal while the grinding energy significantly decreased. A decreased power requirement was also noticeable when milling the blend with wood chips torrefied at 325 °C and pellets torrefied at 325 °C when compared with pure coal, but the mass fraction of large particles in the product increased for these blends. Co-milling coal with wood chips torrefied at 210 °C was not possible in these experiments. The pretreatment of woody biomass materials has the potential of co-firing at higher biomass rates in existing pulverized coal fired power plants without performing significant modifications.